Perspectives of Hydrogen Fuel Cells in Aviation (Texas Journal of Multidisciplinary Studies, 2022)
This article deals with perspectives of hydrogen fuel cells in aviation sphere. It should be noted that Hydrogen fuel cells are emerging as a high-potential technology that offers significant energy efficiency and decarbonisation benefits to a range of industries – including automotive and heavy transport. This paper presents and discusses the classification, working principles, characteristics, and critical technologies of hydrogen fuel cells. Additionally, future technologies and development, including the high-power density motors, converters, power supplies, are discussed for the hydrogen fuel cells in aviation industry.